2023
DOI: 10.1108/acmm-07-2023-2858
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on corrosion resistance of Zn–Al–Mg alloy coating of high-strength steel wires for bridge cables

Donghui Hu,
Shenyou Song,
Zongxing Zhang
et al.

Abstract: Purpose This paper aims to figure out the conundrum that the corrosion resistance longevity of steel wires for bridge cables was arduous to meet the requirements. Design/methodology/approach The “two-step” hot-dip coating process for cable steel wires was developed, which involved first hot-dip galvanizing and then hot-dip galvanizing of aluminum magnesium alloy. The corrosion rate, polarization curve and impedance of Zn–6Al–1Mg and Zn–10Al–3Mg alloy-coated steel wires were compared through acetate spray tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Batch hot-dip galvanizing will form a protective coating structure in the temperature range of 440°C -480°C. Figure 2 shows the growth diagram of the Fe-Zn alloy layer (Hu et al, 2023;Bai and Wu, 2002). At t 0 , the steel matrix contacts the molten zinc pool, and the Fe on the surface of the matrix dissolves rapidly in the zinc pool.…”
Section: Microstructure and Properties Of Each Sublayer Of The Hot-di...mentioning
confidence: 99%
See 1 more Smart Citation
“…Batch hot-dip galvanizing will form a protective coating structure in the temperature range of 440°C -480°C. Figure 2 shows the growth diagram of the Fe-Zn alloy layer (Hu et al, 2023;Bai and Wu, 2002). At t 0 , the steel matrix contacts the molten zinc pool, and the Fe on the surface of the matrix dissolves rapidly in the zinc pool.…”
Section: Microstructure and Properties Of Each Sublayer Of The Hot-di...mentioning
confidence: 99%
“…The sublayers assume a crucial role in the coating formation process, exhibiting distinct physical properties and electrochemical corrosion behaviors. Therefore, it is worth studying the corrosion behavior of these sublayers to further understand the corrosion resistance mechanism of the hot-dip galvanized coating (Hu et al, 2023;Hu et al, 2023;Bai and Wu, 2002;Li et al, 2022aLi et al, , 2022bLi et al, , 2022cLi et al, ,,2022d).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have been conducted to compare the performance of Al-Zn coatings with different processes (dos Santos et al , 2015; Edavan and Kopinski, 2009; Alvarenga and Lins, 2016). The corrosion resistance of three-component alloy coatings has also been investigated (Lee et al , 2019; Hu et al , 2023). Zhang et al (2018) demonstrated that the behaviour of the galvalume was similar as a bare Al sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the addition of Mg and Al elements to the molten bath undergoes eutectic reactions, resulting in the generation of various alloy phases such as MgZn 2 , which may form the Zn/MgZn 2 binary eutectic phase or Zn/Al/MgZn 2 ternary eutectic phase. These alloy phases, or the eutectic phase of zinc, exhibit preferential corrosion, reducing the dissolution rate of zinc, and thereby improving the corrosion resistance of the coating [4,[15][16][17]. The amount of Mg and Al added into the molten bath also affects the structure and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%